A Pilot Study of Concurrent Lead and Cotinine Screening for Childhood Tobacco Smoke Exposure: Effect on Parental Smoking. Issue 5 (May 2014) - Joseph, Anne; Murphy, Sharon; Thomas, Janet; Okuyemi, Kolawole S.; Hatsukami, Dorothy; Wang, Qi; Briggs, Anna; Doyle, Brandon; Winickoff, Jonathan P.
Purpose: To investigate whether a biomarker screening approach for tobacco smoke exposure (TSE) conducted concurrently with lead screening at well-child visits would increase parental smoking cessation and implementation of home smoking restrictions. Design: Observational, quasi-experimental. Setting: Pediatric clinic in Minneapolis, Minnesota. Subjects: Eighty parents who smoked and their children presenting for well-child visits. Intervention: Children in the intervention group had serum cotinine measured with lead screening. Laboratory results were sent to providers and parents and a counselor proactively contacted parents to offer an eight-session telephone intervention to help parents stop smoking. The comparison group, a historical control, received usual care. Measures: Parental smoking, engagement in tobacco treatment, and home and car smoking policies 8 weeks later. Analysis: Mean/standard deviation for continuous data or frequency/percentage for categorical data. Results: Eighty-four percent of eligible parents agreed to have their child tested for TSE along with lead testing. Measurable cotinine was identified in 93% of children. More parents in the intervention group received tobacco treatment than in the comparison group (74% vs. 0%) and more parents reported 7-day point-prevalent abstinence from smoking at 8 weeks (29% vs. 3%). Conclusion: These data demonstrate the feasibility of adding cotinine measurement to routine well-child lead screening to document TSE in small children. Data suggest providing this information to parents increases engagement in tobacco treatment and prompts smoking cessation.